2019
DOI: 10.1016/j.ijid.2018.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of microarray-based serological assay for Crimean-Congo hemorrhagic fever (CCF) and determination of the prevalence of CCFV in Guinea

Abstract: classified as ZIKV seropositive and the remaining 12 (16.7%) as flavivirus seropositive. Eleven of 14 provinces contributed ZIKV positive specimens, ranging from 4.5% of specimens from North Sumatra, Banten, and East Kalimantan to more than 18% of specimens from Central Java. Overall ZIKV seroprevalence in the 1-4 year-old cohort was 9.1%.Conclusion: We have conducted ZIKV serological screening on samples collected from children in representative areas in Indonesia and revealed the seroprevalence of ZIKV in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In total, 15.9% of acute febrile illnesses had bacterial etiology in our study. Similarly, DNA from at least one pathogenic bacterium were identified in 80/440 (18.2%) of the samples from febrile patients in Senegal (35,30,23, 2, and 1 cases for Borellia crocidurae, Rickettsia felis, Bartonella spp., Coxiella. burnetii, and Tropheryma whipplei identification, respectively [46].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In total, 15.9% of acute febrile illnesses had bacterial etiology in our study. Similarly, DNA from at least one pathogenic bacterium were identified in 80/440 (18.2%) of the samples from febrile patients in Senegal (35,30,23, 2, and 1 cases for Borellia crocidurae, Rickettsia felis, Bartonella spp., Coxiella. burnetii, and Tropheryma whipplei identification, respectively [46].…”
Section: Discussionmentioning
confidence: 95%
“…Some previous evaluation work has been performed with the microarray [ 22 , 23 , 28 , 29 , 30 , 31 , 32 ]. Negative control samples were taken from Russian healthy donors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray detects IgM/IgG distinctly but in one well because of the use of Cy3/Cy5-labeled particular Ab. The researchers demonstrated that the recently advanced microarray is a very accurate and specific diagnostic instrument [ 161 ].…”
Section: Advanced Detectionmentioning
confidence: 99%